2019
DOI: 10.1101/600296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cognitive Improvements after Intermittent Deep Brain Stimulation of the Nucleus Basalis of Meynert in a Transgenic Rat Model for Alzheimer’s disease; a Preliminary Approach

Abstract: BackgroundDeep brain stimulation (DBS) of the nucleus basalis of Meynert (NBM) has shown to have promising results in a pilot study with patients suffering from Alzheimer’s disease (AD). A recent study in aged monkeys shows a novel intermittent stimulation pattern to have superior cognitive benefits over continuous paradigms.Objective/HypothesisWe aimed at comparing the cognitive effects elicited by intermittent and continuous NBM stimulation paradigms in an animal model for AD (TgF344-AD rat line; TG), i.e. r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…A general trend in favor of decreasing volumes for all principal cells sublayers findings in our study (see Fig. 2A and Table 1) provide evidence of degeneration in Tg rats corresponds to that reported by other groups [31][32][33], including a denser capillary network in PCL comparing to the entire hippocampus of Tg rats. Furthermore, the average microvessels length in the denser microvascular network of hippocampus in Tg rats was twice that in the hippocampus of non-Tg rats.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A general trend in favor of decreasing volumes for all principal cells sublayers findings in our study (see Fig. 2A and Table 1) provide evidence of degeneration in Tg rats corresponds to that reported by other groups [31][32][33], including a denser capillary network in PCL comparing to the entire hippocampus of Tg rats. Furthermore, the average microvessels length in the denser microvascular network of hippocampus in Tg rats was twice that in the hippocampus of non-Tg rats.…”
Section: Discussionsupporting
confidence: 90%
“…In the past two decades transgenic (Tg) mouse models of AD have shown the vascular consequences of expression of human AD mutants and deposition of A␤ peptides [8,9,23,24,26,30]. The overexpression of familial AD-related mutations in rats [31][32][33] has further advantages due to the closer evolutionary relationship between humans and rats; and, the relative higher behavioral complexity of rats compared to mice [34]. Here we report on the TgF344-AD model that overexpresses the human APPswe and PS1 E9 mutation under the mouse prion protein promoter [21] in the Fischer 344 rat.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, using Barnes maze test, a preliminary study reported the presence of hippocampus‐dependent spatial reference learning deficits at the age of 15 months 14 but other studies did not measure differences in age 6, 20 13 13 and 15 months 15 . A simplified version of this test made it possible to show memory alterations at the age of 18 months 21 . During the Morris water maze test which also involves the hippocampus function, it has been reported that there was no memory deficits at the age of 4–6, 22,23 7–11, 23 15 20 and 24 months 15,20 despite a lack of precision to find the platform 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The topography and morphological structure of the NBM are different between rodents and primates, including differences in the circuitry distribution of cholinergic neurons within this region and the degree of afferent and efferent fibres from NBM subdivisions, which could account for species-dependent outcome of behavior in experimental settings [27]. Similar to our findings, Koulousakis et al 2020, has found beneficial spatial memory effects in the modified Barnes maze following acute intermittent NBM DBS using 60 Hz, monophasic pulses, 100 µs and 200 µA in an Alzheimer rat model [11]. Interestingly, the authors did not find any effects on recognition memory.…”
Section: Discussionsupporting
confidence: 77%